Protein Kinase C Epsilon Overexpression Is Associated With Poor Patient Outcomes in AML and Promotes Daunorubicin Resistance Through p-Glycoprotein-Mediated Drug Efflux - Nicholson, Rachael; Menezes, Ana Catarina; Azevedo, Aleksandra; Leckenby, Adam; Davies, Sara; Seedhouse, Claire; Gilkes, Amanda; Knapper, Steve; Tonks, Alex; Darley, Richard L. (Frontiers in Oncology, 2022)
The protein kinase C (PKC) family of serine/threonine kinases are pleiotropic signaling regulators and are implicated in hematopoietic signaling and development. Only one isoform however, PKCε, has oncogenic properties in solid cancers where it is associated with poor outcomes. Here we show that PKCε protein is significantly overexpressed in acute myeloid leukemia (AML; 37% of patients). In addition, PKCε expression in AML was associated with a significant reduction in complete remission induction and disease-free survival. Examination of the functional consequences of PKCε overexpression in normal human hematopoiesis, showed that PKCε promotes myeloid differentiation, particularly of the monocytic lineage, and decreased colony formation, suggesting that PKCε does not act as an oncogene in hematopoietic cells. Rather, in AML cell lines, PKCε overexpression selectively conferred resistance to the chemotherapeutic agent, daunorubicin, by reducing intracellular concentrations of this agent. Mechanistic analysis showed that PKCε promoted the expression of the efflux pump, P-GP (ABCB1), and that drug efflux mediated by this transporter fully accounted for the daunorubicin resistance associated with PKCε overexpression. Analysis of AML patient samples also showed a link between PKCε and P GP protein expression suggesting that PKCε expression drives treatment resistance in AML by upregulating P-GP expression.